National Academic Decathlon 2015 Video Montage - Ricky Guing, Fitzpatrick (YouTube, 2015)
National Academic Decathlon 2015 Video Montage, which was held recently at Unimas from 11-12 April 2015. The event was held at Central Teaching Facilities 2. Centre of Applied Learning & Multimedia (CALM) was responsible for managing the venue and provided the audio/ visual requirements for the organisers.